Acquired von Willebrand syndrome after continuous-flow mechanical device support contributes to a high prevalence of bleeding during long-term support and at the time of transplantation - Uriel, Nir; Pak, Sang-Woo; Jorde, Ulrich P; Jude, Brigitte; Susen, Sophie; Vincentelli, Andre; Ennezat, Pierre-Vladimir; Cappleman, Sarah; Naka, Yoshifumi; Mancini, Donna (Journal of the American College of Cardiology, 2010)
The objective of the study was to determine the prevalence of bleeding during continuous-flow left ventricular assist device support and to identify potential mechanisms for those bleeding events. Bleeding is frequently reported with continuous-flow left ventricular assist devices and may result from anticoagulation coupled with bleeding diathesis such as acquired von Willebrand syndrome. Accordingly, the prevalence of coagulation abnormalities including laboratory assessment for von Willebrand syndrome, bleeding events during device support, and at heart transplantation were evaluated. A retrospective study in all HeartMate II (HM II) (Thoratec Corp., Pleasanton, California) patients who underwent implantation between April 1, 2004, and August 1, 2009, was performed. Bleeding was defined as the need for transfusion >7 days after device insertion of 1 U of packed red blood cells. Transfusion at heart transplantation was compared with that in HeartMate XVE patients. Seventy-nine HM II devices were implanted. Anticoagulation included warfarin in 68.3%, aspirin in 55.7%, and dipyridamole in 58.2% of the patients. Of the patients, 44.3% had bleeding episodes at 112 ± 183 days after left ventricular assist device implantation, with 50% experiencing an event within 2 months. Gastrointestinal bleeding was the most frequent event. At the index event, the international normalized ratio averaged 1.67 ± 0.53, and the platelet count was 237 ± 119 × 10(9)/l. Comparison of the transfusion requirements at heart transplantation of 35 HM II patients with 62 HeartMate XVE patients demonstrated twice the transfusion requirements in HM II patients (packed red blood cells, 6.3 ± 0.8 U vs. 3.8 ± 0.5 U; platelets, 12.5 ± 5.4 U vs. 8.6 ± 6.4 U; fresh frozen plasma, 9.6 ± 4.9 U vs. 4.9 ± 3.6 U; and cryoprecipitate, 4.3 ± 3.6 U vs. 2.2 ± 3.5 U; p < 0.05 for all). High molecular weight von Willebrand factor multimers were measured in 31 HM II patients and were reduced in all patients; 18 of these 31 (58%) patients had bleeding. Patients with the HM II had a high incidence of bleeding events during device support and at heart transplantation. All HM II patients had reduced high molecular weight von Willebrand factor multimers. The role of these abnormalities in the high incidence of bleeding deserves further investigation. Furthermore, alterations in anticoagulation should be considered during device support and before surgery in patients supported with the HM II.